P130 Fifteen-minute consultation: the infant with a small head. (June 2019) - Alexander, Joshua; Bholah, Nusrat; Okigbo, Naomi; Devlin, Ruth; Betts, Aisling; Healy, Jack; Higgins, Sarah; Meehan, Judith; Molloy, Eleanor
Abstract : Aims: Microcephaly is a feature of multiple diseases, and has a vast array of aetiologies. Thus, identifying this condition clinically is only the start of establishing a diagnosis. Early assessment, analysis, and identification is vital to aiding the patient and family in managing the microcephaly itself, as well as future complications that may arise as a result. We aim to provide general practitioners, paediatricians and other health professionals, with a framework for initial approach to a patient presenting with a small head. Methods: An electronic review of literature on databases PubMed, Google Scholar, and Science Direct was performed searching Title/Abstract with the terms: [Microcephaly AND (assessment OR consultation OR examination)]. Previously published guidelines with information on initial approach to the microcephalic patient were also used in production of the proposed protocol. Results: We devised a protocol which helps clinicians to firstly diagnose microcephaly, and then separate primary microcephaly from secondary microcephaly. We then outlined potential investigations that should be undertaken to identify any underlying conditions. For primary microcephaly, specialised cytogenetic studies and gene sequencing and use of microarray can help to diagnose syndromes resulting in microcephaly. [i] Secondary microcephaly is investigated through a comprehensive viral screen and range of biochemical blood tests to identify underlying causes. [ii] The above methods are often combined with various imaging modalities, commonly MRI brain. Conclusion: As microcephaly is a clinical finding rather than a disease, a careful clinical history and examination are the cornerstones of the consultation, with findings guiding further investigations. Reference: Woods CG, Parker A. Investigating microcephaly. Archives of Disease in Childhood . 2013;98(9):707–713. Michels T, Morris M, Myers T. Microcephaly. [internet]. 2009. Available from: https://core.ac.uk/download/pdf/62772193.pdf